Ancylomenes kuboi and A. okunoi spp. nov. (Decapoda: Pontoniinae), from the Australian Northwest Shelf, Vietnam and the Philippines - Bruce, A. J. (Zootaxa, 2010)
Two new species of Ancylomenes (Decapoda: Pontoniinae), A. kuboi sp. nov. (Australian northwestern shelf and Vietnam, from 9.2–82 m) and A. okunoi sp. nov., (Australian north-western shelf and the Philippines, from 80–134 m, are described and illustrated. Both are most closely related to A. tosaensis (Kubo, 1951), also found on the Northwest Shelf, and a key for their separation is provided.